2019
DOI: 10.1590/0100-3984.2018.0118
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic criteria of vermiform appendix on computed tomography and a possible risk of developing acute appendicitis

Abstract: Objective: To evaluate the correlation of morphological criteria of the cecal appendix using computed tomography (CT) and the possible risk of developing acute appendicitis. Materials and Methods: Cases were defined as patients with surgically confirmed acute appendicitis who had undergone CT at least twice: at diagnosis and at least one month prior. Controls were defined as emergency patients with abdominal pain who had undergone abdominal CT that excluded acute appendicitis and had also undergone CT at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Appendiceal enlargement can be an isolated finding of appendicitis and was reported in up to 48% of symptomatic individuals 12 . The diameter cut-off of 6 mm was helpful to diagnose appendicitis 12 , 20 , 25 . In their study, appendicitis was not found in any patients who had appendiceal diameter less than 6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal enlargement can be an isolated finding of appendicitis and was reported in up to 48% of symptomatic individuals 12 . The diameter cut-off of 6 mm was helpful to diagnose appendicitis 12 , 20 , 25 . In their study, appendicitis was not found in any patients who had appendiceal diameter less than 6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Cabe mencionar que, existen estudios realizados en población sin sospecha clínica de apendicitis, donde se ha encontrado que en el 42% de pacientes, el diámetro apendicular normal puede llegar de 6 a 10 mm, atribuyendo estos valores a la presencia de contenido como aire intraluminal. Por lo tanto, el diámetro apendicular tomográfico aumentado, en un escenario de pacientes sin alta sospecha clínica de apendicitis aguda, podría conducir a resultados falsos positivos [28][29][30][31] .…”
Section: Discussionunclassified